Exploring seismic fragility and strengthening of masonry built heritage in Lisbon (Portugal) via the Applied Element Method - Salvalaggio, Matteo (2024)
Although mainland Portugal has been spared from large magnitude earthquakes in recent years, it faces a threat due to the presence of several active fault systems. In such a framework, Portuguese pre-code masonry construction is believed to be the most vulnerable in the existing building stock. Given the lack of information on earthquake damage to this stock, the use of detailed numerical models is a viable strategy to comprehend its seismic behavior. This paper provides an updated fragility characterization of Lisbon pre-code masonry buildings based on their seismic assessment through the Applied Element Method. To limit the computational time, a promising pushover strategy, known as Incremental Ground Acceleration, was adopted. After the characterization of the current fragility, two retrofit layouts based on piers strengthening were modeled and assessed for the building stock whose seismic capacity does not meet expected demand. The aim of the paper is to derive updated fragility curves for the Lisbon region to support risk analysis incorporating the latest hazard studies and to offer insights into potential retrofit interventions.